The Faculty of Intensive Care Medicine Workforce Survey – What impacts on our working lives? - Grailey, KE (J Intensive Care Soc, 2018)
The Faculty of Intensive Care Medicine distributes an annual survey to its Consultants, allowing the evaluation of workforce profile, working patterns and the opportunity for analysis of key information on issues affecting these. We undertook an exploratory review of the data provided within the 2016 survey, with the aim of identifying themes within respondents stated career intentions and associated factors. Given the modest (36%) response rate, we are unable to draw conclusions with certainty, but there are indications within the data that the UK Intensive Care Medicine consultant body is facing significant stressors whilst at work, due to working patterns and limited resources. The data within the 2016 survey provide a base from which to develop future Faculty of Intensive Care Medicine workforce surveys that will extract data about the positive aspects of a career in intensive care medicine. The survey data provide a signal that there may be significant potentially modifiable stressors for intensive care doctors, and as such affords support for initiatives to improve job planning and sharing of implemented solutions, as well as a need to focus on workforce wellbeing as an important and necessary contributor to patient safety within intensive care medicine.